Improving Religious Literacy in Muallaf in Pituruh Sub- District, Purworejo District - Astuti, Wiji; Aziz, Abdul (Islamic Extension Guidance Study Program (BPI) of the Faculty of Da'wah and Communication, 2023)
Abstrak: Penelitian ini bertujuan untuk mendeskripsikan pemahaman keagamaan para muallaf di Kecamatan Pituruh Kabupaten Purworejo dan menganalisis strategi pelaksanaan penyuluh Islam dalam meningkatkan literasi agama pada muallaf serta mengidentifikasi faktor pendukung dan faktor penghambat penyuluh agama Islam dalam meningkatkan literasi agama pada muallaf di Kecamatan Pituruh Kabupaten Purworejo. Penelitian ini menggunakan penelitian lapangan yang berbentuk deskriptif kualitatif. Dalam rangka mendapatkan data yang dibutuhkan, penulis menggunakan teknik observasi partisipatif, wawancara dan dokumentasi. Sumber informasinya adalah kepala KUA dan penyuluh Agama Islam Kecamatan Pituruh dan Muallaf di Kecamatan Pituruh. Hasil penelitian menunjukkan bahwa strategi pelaksanaan penyuluhan agama Islam dalam meningkatkan literasi agama pada muallaf adalah ceramah dan silaturahmi. Jenis ceramahnya adalah khutbah Jum’at, ceramah ramadhan dan ceramah majlis taklim. Faktor pendukung penyuluh agama dalam meningkatkan literasi agama pada muallaf yaitu banyaknya majlis taklim yang sudah terbentuk di setiap desa, sarana transportasi yang memadai, banyaknya masjid dan mushola, mayoritas masyarakat beragama Islam dan ormas Islam yang sedang gencar dibentuk. Sedangkan faktor penghambat penyuluh agama islam dalam meningkatkan literasi agama pada muallaf adalah kurangnya jumlah penyuluh, status muallaf dan perbedaan pendapat mengenai agama.Abstract: This study aims to describe the religious understanding of converts in Pituruh Subdistrict, Purworejo Regency and to analyze the implementation strategy of Islamic instructors in increasing religious literacy in converts and to identify supporting factors and inhibiting factors of Islamic religious instructors in increasing religious literacy in converts in Pituruh Subdistrict, Purworejo Regency. This study uses field research in the form of qualitative descriptive. In order to obtain the required data, the authors used participatory observation techniques, interviews and documentation. The source of the information was the head of the KUA and Islamic Religious Education instructors in the Pituruh and Muallaf sub-districts in the Pituruh sub-district. The results of the study show that the strategy for implementing Islamic religious counseling in increasing religious literacy in converts is lectures and hospitality. The types of lectures are Friday sermons, Ramadan lectures and majlis taklim lectures. Factors supporting religious instructors in increasing religious literacy among converts are the large number of majlis ta'lim that have been formed in each village, adequate transportation facilities, the large number of mosques and prayer rooms, the majority of Muslim communities and Islamic mass organizations which are being intensively formed. Meanwhile, the inhibiting factors for Islamic religious instructors in increasing religious literacy among converts are the lack of number of instructors, the status of converts and differences of opinion regarding religion.